Faktor- Faktor Yang Mempengaruhi Ibu Dalam Pemberian Mpasi Dini Di Polindes Temuan Sari Kabupaten Musi Rawas - Rohani, Tuti; Umami, Desi Aulia; Nurbayanti, Anggi (Universitas Dehasen Bengkulu, 2025)
Improper EARLY provision of MP-ASI not only disrupts the nutritional intake that the baby should get, but also disrupts the baby's digestion because the digestive system is not yet able to digest or break down the food. Coverage of exclusive breastfeeding for babies 0-6 months in the Sari Findings Polindes Working Area, Musi Rawas Regency is still low. The aim of this research is to determine the factors of giving early MP ASI to babies 0-6 months in the Polindes Teman Sari Work Area, Musi Rawas Regency. The design of this research is descriptive analytic with a cross sectional approach. The sample for this research was all mothers who had babies aged (0-6) months who were in the working area of ​​Polindes Teman Sari, Musi Rawas Regency, totaling 63 people. This research uses univariate and bivariate analysis. The results of the univariate analysis of this research show that of the 63 respondents, almost half (49.2%) have a supportive attitude, more than half (54.0%) work, almost half (44.4%) have supportive husbands and more than half ( 61.9%) who provide Early MP ASI. The results of the bivariate analysis showed that attitudes had a value of p = 0.001 ≤ α = 0.05, mother's work had a value of p = 0.005 ≤ α = 0.05 and husband's support had a value of p = 0.007 ≤ α = 0.05. The results of this research show that the attitudinal variable is most associated with giving early MP ASI to babies aged 0-6 months at Polindes Teman Sari, Musi Rawas Regency.